Fault Tolerance for Complex System - Chan, Shi Jing; Pebrianti, Dwi; M. F., Abas; Luhur, Bayuaji (Universiti Malaysia Pahang, 2016)
Fault Tolerance (FT) enables system to continue operating despite event of failures. Therefore, FT is served as a backup component or procedure that can immediately play its role without incurring any service lost. FT exists in many form, where it can either be the software or hardware or both the hardware and software. Fault Tolerance is an umbrella term for fault detection, fault isolation, fault identification and fault solving for all types of fault. For the purpose of visualizing the fault detection and isolation process, a two wheel robot is used in this study as a representation of a complex system. The aim of this research is to construct and design a new Fault Tolerance algorithm. The proposed method for the fault tolerant is aimed to solve the fault in actuator or in the sensor by resetting and adjusting it to the correct position. The technique used is able to recognize the different fault from its data condition through the system sensors or actuator. This combined method is served as an innovative solution to identify a fault and solve it immediately.